ANALYSIS OF TRAFFICS HIGHWAY NETWORK CAPACITY IN PEKANBARU CITY BY USING MAXIMUM FLOW TECHNIQUE - Iwan Nauli Daulay (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
The research was conducted in Pekanbaru city aims to know capacity of highwaynetwork include the mean of vehicle velocity and forecast amount of vehicleespecially four wheel vehicle, so the implication would be usefull especially forthe Goverment to develop infrastructure and improving traffic management in thefuture.Refering to source and spesification of the data required consist of primary andsecondary data. Primary data taken by using observation technique andsecondary data taken by using documentary technique at Badan Pusat StastistikPekanbaru. The technique of vehicle forecasting done by using trend projectionwith time series data consideration ceteris paribus, and capacity of highwaynetwork and the detail point to point capacity analysing by using maximum flowtechnique method.The result would descibe capacity of highway network in all around Pekanbaru is6,437 vehicle per hour and the mean of velocity was 35,6 km per hour in 2012.The amount of four wheel vehicle increase until 47,9 % for 2017 next five yearsfrom 2012, so the mean of vehicle velocity will be 26,15 km per hour. In 2022vehicle increase to 87,2 % and mean of velocity 20,6 km per hour. The suggestionall of this indicate the goverment must anticipate for develop infrastucture andimproving traffics policy.Kata Kunci : capacity, velocity, forecasting, infrastucture, traffics.